2016
DOI: 10.3920/jiff2015.0090
|View full text |Cite
|
Sign up to set email alerts
|

Insects and other invertebrates in the Pjiekakjoo (Tlahuica) culture in Mexico State, Mexico

Abstract: The Pjiekakjoo are the smallest indigenous group in the State of Mexico. They have managed to survive and maintain an ethnic project despite their proximity to the largest metropolitan areas in central Mexico: Mexico City, Toluca and Cuernavaca. Sadly, their indigenous language is considered to be in danger of extinction. Their knowledge of insects and other invertebrates was recorded through a collaborative project that included the collection of organisms, semi-structured interviews and intergenerational wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…7 and 8 ). For understanding these relations, the idea of Nahua contemporary knowledge [ 14 ] is helpful, since it reflects the knowledge dynamism and helps to recognize and understand the integrity of diverse sources of coexisting knowledge [ 14 , 17 ] as well as the importance of this knowledge in the present-day world. We identified that although knowledge, beliefs, and practices have a root in the Nahua local ecological knowledge, these are influenced by new elements from direct observation, learning from other people, communitarian intra and inter communication and the media (internet, TV), books, and classes in the school, as well as customs, beliefs, and knowledge from people from outside the community.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 and 8 ). For understanding these relations, the idea of Nahua contemporary knowledge [ 14 ] is helpful, since it reflects the knowledge dynamism and helps to recognize and understand the integrity of diverse sources of coexisting knowledge [ 14 , 17 ] as well as the importance of this knowledge in the present-day world. We identified that although knowledge, beliefs, and practices have a root in the Nahua local ecological knowledge, these are influenced by new elements from direct observation, learning from other people, communitarian intra and inter communication and the media (internet, TV), books, and classes in the school, as well as customs, beliefs, and knowledge from people from outside the community.…”
Section: Discussionmentioning
confidence: 99%
“…LEK expresses not only what people know, but also their representations; non-material expressions that generate collective identity, norms of behaviour towards natural environment, values, forms of use and management of natural resources, and alternatives before stressful natural events [ 3 , 7 ]. Based on Santos [ 13 ], Aldasoro-Maya [ 14 ] proposed adding the term “contemporary knowledge”, considering the importance to recognize that in human communities, different knowledge and experiences commonly coexist, some of which (generally those indigenous and local) are considered to be elements from the past [ 15 , 16 ]. Therefore, the term “contemporary” emphasizes that, although the local/indigenous knowledge has its basis on traditional knowledge generated through processes occurring in thousands of years, it has been and currently is dynamic, under continuous production and reproduction of elements, open, adopting, and adapting before changing factors and different forms of knowledge it coexists with [ 14 , 15 , 17 – 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Berkes [ 38 ] considers that TEK includes associated practices and beliefs. Aldasoro-Maya [ 39 ] assigns the connotation of “contemporary” to these localized bodies of knowledge, emphasizing that although having roots in tradition, they also reflect interactions with other forms of knowledge, cultures and temporality, thus updating their suitability for the actual management of agrobiodiversity conservation. Multifunctionality knowledge is a part of these continuously actualized localized bodies of contemporary knowledge and contributes to the maintaining and renewing of biocultural diversity [ 24 , 31 , 40 ] and the diversification, updating and adaptation of socio-ecological systems such as home gardens [ 2 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%